Registration of provitamin A-enriched tropical maize inbred lines - Menkir, A.; Meseka, S.; Gedil, M.; Ojo, T.; Mengesha Abera, W. (Wiley, 2024)
Vitamin A deficiency and its associated disorders are pervasive in sub-Saharan Africa (SSA) including many middle- and low-income countries across the world. Provitamin A-enriched maize (Zea mays L.) inbred lines with desirable agronomic and adaptive traits have been developed and used to generate and commercialize maize varieties with medium to high levels of provitamin A in a few countries to curb vitamin A deficiency. Nonetheless, these inbred lines have not been made widely available to the public and private sector breeders in many countries. The main purpose for releasing the 21 provitamin A-enriched tropical maize inbred lines (PI 705424–PI 705444, Reg. nos. GP-624–GP-644) is to supply maize breeders with elite source germplasm for increasing provitamin A and other carotenoids to much higher levels to offset losses during storage, natural degradation, and processing. These inbred lines were developed at the International Institute of Tropical Agriculture (IITA) from backcrosses of high β-carotene temperate lines as donors and elite tropical lines as recipients. These inbred lines were developed through repeated self-pollination with rigorous visual selection among and within lines for plant vigor, synchronous silk emergence and pollen shedding, low ear placement, and resistance to lodging and major tropical diseases, followed by selection for bright yellow to orange kernel color with semi flint to flint kernel texture after harvest. The released maize inbred lines will be diverse sources of favorable alleles to accelerate genetic gain in provitamin A and other beneficial carotenoid enrichment for human health.